2012
DOI: 10.1515/jpem-2012-0224
|View full text |Cite
|
Sign up to set email alerts
|

The treatment effect of diazoxide on 44 patients with congenital hyperinsulinism

Abstract: Diazoxide is a first-line treatment of CHI with high safety. Most of the patients with CHI were responsive to diazoxide treatment. Diazoxide should be used as a trial immediately after CHI diagnosis was made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 0 publications
1
17
0
1
Order By: Relevance
“…The incidence of the common adverse effects of diazoxide, like hyponatremia and fluid retention, was not different between the two groups and none of the infants in our study had the other reported adverse effects of diazoxide, such as necrotising enterocolitis, hypertrichosis, refractory hypotension, ketoacidosis and neutropenia. The similar safety profile of diazoxide has been demonstrated by various authors . In our study, the infants showed a good cortisol response at the time of hypoglycaemia and thus demonstrated a relatively adequate counter‐regulatory hormonal response in SGA infants with hypoglycaemia, similar to a previous study from the same unit .…”
Section: Discussionsupporting
confidence: 90%
“…The incidence of the common adverse effects of diazoxide, like hyponatremia and fluid retention, was not different between the two groups and none of the infants in our study had the other reported adverse effects of diazoxide, such as necrotising enterocolitis, hypertrichosis, refractory hypotension, ketoacidosis and neutropenia. The similar safety profile of diazoxide has been demonstrated by various authors . In our study, the infants showed a good cortisol response at the time of hypoglycaemia and thus demonstrated a relatively adequate counter‐regulatory hormonal response in SGA infants with hypoglycaemia, similar to a previous study from the same unit .…”
Section: Discussionsupporting
confidence: 90%
“…The conservative treatment constitutes primarily of diazoxide, or octreotide, as first choice, but a significant number of the patients are unresponsive or only partially responsive to medical treatment . Alternatively, continuous glucagon, sirolimus or nifedipine among others have been used, however with variable success .…”
Section: Introductionmentioning
confidence: 99%
“…Congenital hyperinsulinism (CHI) is the most common cause of persistent hypoglycemia in neonates and infants. [1][2][3][4] Immediate evaluation and early diagnosis of CHI are important for initiating the appropriate treatment because of the increased risk of permanent brain injury secondary to the metabolic actions of insulin. 2 Most cases of CHI may persist for the first week/month of life before improving spontaneously.…”
Section: Introductionmentioning
confidence: 99%
“…5 Diazoxide is a benzothiadiazine derivative, a peripheral vasodilator mainly used for hypertensive emergencies. [2][3][4]6 The agent increases membrane permeability to potassium ions in the vascular smooth muscle, thereby stabilizing the membrane action potential and preventing vascular smooth muscle contraction. 6 It also inhibits insulin release by interacting with adenosine triphosphate-sensitive potassium channels of pancreatic islet β-cells.…”
Section: Introductionmentioning
confidence: 99%